DEVELOPMENT OF «ROAD MAP» OF INCREASE OF EFFICIENCY OF FINANCING NIR OF HIGHER EDUCATION INSTITUTIONS - Alexander E. Vorobev (Статистика и экономика)
Various ways of ﬁnancing of universityscience are considered. The ratio in ﬁnancing of university science of varioussources are presented. Possibilities ofsale of the patented technologies areshown.